A Theological Study of Jesus’ Leadership and Management as the Foundation of Church Ministry - Windarti, Maria Titik; Ming, David; Sirait, Junio Richson (Jurnal Teologi (JUTEOLOG), 2025)
This theological study explores the nature and implementation of Jesus’ leadership and management as a foundational paradigm for church ministry. Utilizing a phenomenological methodology within a naturalistic paradigm and grounded in a qualitative research approach, data were gathered through observation, in-depth interviews, and comprehensive literature analysis. The findings reveal a significant disparity in the understanding and application of Jesus’ leadership and management principles within ecclesial contexts. This discrepancy is primarily attributed to four interrelated factors: (1) insufficient comprehension of the foundational concepts of Jesus’ leadership and management, (2) a lack of clarity regarding their intended purpose within ministry,(3) weak strategic alignment with Jesus’ leadership model, and(4) the  absence of Christlike character in the exercise of leadership roles within the church. Drawing upon theological frameworks and empirical insights, the study proposes a contextualized model for integrating the leadership and management of Jesus as a core foundation for effective and faithful church ministry. The research outcomes offer practical implications for local congregations in Indonesia and serve as a reference point for future theological and pastoral scholarship. All reflections and recommendations are ultimately directed toward the glorification of God.